Model Pengelolaan Hipertensi Berbasis Masyarakat : Edukasi, Senam Hipertensi, dan Terapi Jus Mentimun di Lenteng Agung Jakarta Selatan (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Hypertension is a public health problem that requires educational approaches and nonpharmacological interventions. This community service activity aimed to improve knowledge and support community-based hypertension management through health education, hypertension exercise, and cucumber juice therapy in RT 03 RW 08 Lenteng Agung, South Jakarta. The activity was conducted in three stages. The preparation stage included site selection, door-to-door screening of individuals with hypertension, which identified 32 hypertensive residents, obtaining informed consent, and preparing the instruments. The implementation stage consisted of hypertension education with pre-test and post-test knowledge assessments, as well as demonstrations of hypertension exercise and cucumber juice preparation involving 29 participants. Participants were encouraged to perform the exercise and consume cucumber juice regularly for seven days at home. The evaluation stage assessed changes in blood pressure after the intervention. The results showed improved knowledge and reduced blood pressure in most participants. This activity was effective in supporting hypertension management in the community.